2017
DOI: 10.1016/j.juro.2017.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Impact of Diet, Fluid Intake, Caffeine, Alcohol and Tobacco on Lower Urinary Tract Symptoms: A Systematic Review

Abstract: Purpose Foods, fluid intake, caffeine, alcohol, and tobacco may influence lower urinary tract symptoms (LUTS). Changes in these potentially modifiable non-urologic factors (NUF) are often suggested to improve LUTS. To better understand the relationship of NUFs with LUTS, we performed a systematic literature review to examine, grade, and summarize reported associations between LUTS and diet, fluid intake, caffeine, tobacco and alcohol use. Materials and Methods We performed PubMed searches for eligible articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 51 publications
4
60
2
1
Order By: Relevance
“…They found no association with UI incidence, 10,11 or "unclear", "limited", "conflicting" or "mixed" results for various LUTS. 12,13 Yet, one review including studies on both human and animal models concluded that high caffeine doses may have a possible role in two LUTS, namely urinary frequency and urgency episodes-the latter being in line with our conclusions. 13 Caffeine is generally considered a mild diuretic, 55 with an increased water excreting action, especially for doses above 250 mg. 56 Consequently, while the diuretic effect is less certain for daily consumers due to habituation, caffeine intake could generally accelerate urine production.…”
Section: Discussionsupporting
confidence: 86%
“…They found no association with UI incidence, 10,11 or "unclear", "limited", "conflicting" or "mixed" results for various LUTS. 12,13 Yet, one review including studies on both human and animal models concluded that high caffeine doses may have a possible role in two LUTS, namely urinary frequency and urgency episodes-the latter being in line with our conclusions. 13 Caffeine is generally considered a mild diuretic, 55 with an increased water excreting action, especially for doses above 250 mg. 56 Consequently, while the diuretic effect is less certain for daily consumers due to habituation, caffeine intake could generally accelerate urine production.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, recent a meta-analysis found that the periodontal disease may be positively associated with an increased risk of BPH (Wu et al, 2019). In addition, research has shown that the long-term excessive consumption of alcohol, diuretics, dicyclomine, and caffeine may also contribute to LUTS, although moderate levels of alcohol intake have been shown to reduce the incidence of BPH (Bradley et al, 2017). At present, BPH can be treated by both non-pharmacological and pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral self‐management treatments, including pelvic floor muscle training, behavioral strategies, and fluid management, as first‐line treatment for UI, are supported by high levels of evidence from several systematic reviews and clinical practice guidelines . Behavioral interventions have proven efficacy for reducing UI and improving quality of life . Behavioral self‐management programs are multifaceted interventions that rely on patient education and active patient participation.…”
Section: Introductionmentioning
confidence: 99%